SERUM BIOCHEMICAL DETERMINATIONS OF PROPOLIS-TREATED RATS - Sforcin, J.m. [UNESP]; Funari, S.r.c. [UNESP]; Novelli, E.l.b. [UNESP] (Centro de Estudos de Venenos e Animais Peçonhentos - CEVAP, Universidade Estadual Paulista - UNESP, 1995)
Ethanolic extracts of the bee glue, a resinous substance collected by honeybees called propolis, have been widely used in folk medicine since ancient times. Antibacterial, antifungal and thus antiseptic properties may represent the basis for the historical and present use of these extracts in dermatology, against inflammatory conditions and common colds. This work was carried out in order to verify possible biochemical alterations in some seric parameters of propolis-treated rats. It was shown that propolis possesses an antioxidant property and its administration did not affect either amylase and alanine transaminase activities or total protein concentration.
Keywords: propolis; serum; biochemistry